The distinctiveness of engagement and flow at work - van Ittersum, Kyle William (Kansas State University, 2015)
Within the literature on engagement at work there has traditionally been a focus on overall work engagement. However, in recent years there has been increasing research on applying a specific form of task engagement, called flow, to the world of work. The current project details two studies that serve to differentiate and understand the relationship between overall work engagement and flow. The first study collected data on engagement and flow from several hundred working adults and used confirmatory factor analysis to explore the factor structure of the two concepts. Results indicated that flow and engagement are separate constructs, albeit related. The second study again collected data from working adults, however, the goal was to show the differential relationships both flow and engagement have with the work outcomes of job satisfaction, commitment, citizenship behaviors, and burnout. Results indicated that both flow and engagement were significant predictors of these outcomes with engagement being the stronger predictor of the two. Theoretical and practical implications of these findings are also discussed in full.
Keywords: Flow; Work Engagement; Job Satisfaction; Organizational Commitment; Burnout; Organizational Behavior (0703); Psychology (0621)